EFEKTIVITAS MEDIA VIDEO PEMBELAJARAN TERHADAP HASIL BELAJAR SISWA SD - Fahri Anwari; Asep Sahrul Gunawan (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to analyze the effectiveness of using educational video media on elementary school students’ learning outcomes, map the variations of its impact across different subjects, and identify the supporting and inhibiting factors in its implementation. The research method employed in this study is a literature review. Data collection was conducted through documentation techniques by searching national scientific journal articles in the Google Scholar database using strict inclusion criteria. The collected data were analyzed descriptively and qualitatively through the stages of data reduction, data presentation, and conclusion drawing. The results of the study indicate that the use of educational video media consistently and significantly improves elementary school students’ learning outcomes. Indicators of success are demonstrated by increased post-test scores, high effect size values, and improved learning mastery. Educational video media has also been proven to increase students’ learning motivation, attract students’ attention, and help students understand abstract concepts more concretely. The effectiveness of video media becomes more optimal when integrated with innovative student-centered learning models, such as cooperative learning. Therefore, educational video media can serve as an effective instructional tool to improve the quality of elementary school students’ learning outcomes. Keywords: Effectiveness, Educational Video, Learning Outcomes, Elementary School Students, Literature Review.